From tradition to progressiveness: Analyzing Thailand's image on youtube amid post-cannabis legalization. - Ibtesam Mazahir; Smith Boonchutima; Safeena Yaseen (PLoS ONE)
This research examines the depiction of Thailand on YouTube subsequent to the nation's decision to legalize recreational marijuana in June 2022. By analyzing 57 video clips recorded between March and September 2022, we investigate the evolution of Thailand's digital image after the legalization of cannabis in the country. The outcomes of our study demonstrate a predominantly favorable account, highlighting the incorporation of marijuana into Thai society, its therapeutic capabilities, and its potential as a lucrative economic commodity. In intimate connection to elements of the social, physical, and cultural components, the emotional dimension developed as a prevailing theme. Thai residents and government officials were the main influencers in shaping the discussion, representing the prevailing public opinion in support of the choice to legalize marijuana. The prevailing media narratives, which included tourism, celebration, and policy, further emphasized the positive perspective on the advantages of legalizing marijuana. This research emphasizes the profound impact of substantial policy changes on a nation's international reputation, with Thailand depicted as providing a distinctive combination of cultural heritage and contemporary elements.